Association between population prevalence of smoking and incidence of meningococcal disease in Norway, Sweden, Denmark and the Netherlands between 1975 and 2009: a population-based time series analysis. Issue 2 (10th February 2014) - Norheim, Gunnstein; Sadarangani, Manish; Omar, Omar; Yu, Ly-Mee; Mølbak, Kåre; Howitz, Michael; Olcén, Per; Haglund, Margaretha; van der Ende, Arie; Pollard, Andrew J
Abstract : Objective: To investigate the relationship between the prevalence of smoking in the population and incidence of invasive meningococcal disease (IMD) among children under 5 years of age. Design: Retrospective, longitudinal, observational study. Poisson regression controlled for confounding factors. Setting: Norway, Sweden, Denmark and the Netherlands between 1975 and 2009. Population: Total population of approximately 35 million people in these four countries. Data sources: Data were collected from the Ministries of Health, National Statistics Bureaus and other relevant national institutes. Results: In Norway, there was a significant positive relationship between the annual prevalence of daily smokers among individuals aged 25–49 years and the incidence of IMD in children under 5 years of age, unadjusted (RR=1.04–1.06, 95% CI 1.02 to 1.07, p<0.001) and after adjustment for time of year (quarter), incidence of influenza-like illness and household crowding (RR=1.05–1.07, 95% CI 1.03 to 1.09, p<0.001). Depending on age group, the risk of IMD increased by 5.2–6.9% per 1% increase in smoking prevalence among individuals aged 25–49 years in adjusted analyses. Using limited datasets from the three other countries, unadjusted analysis showed positive associations between IMD in children related to older smokers in Sweden and the Netherlands and negative associations related to younger smokers in Sweden. However, there were no demonstrable associations between incidence of IMD and prevalence of smoking, after adjustment for the same confounding variables. Conclusions: The reduced incidence of IMD in Norway between 1975 and 2009 may partly be explained by the reduced prevalence of smoking during this period. High-quality surveillance data are required to confirm this in other countries. Strong efforts to reduce smoking in the whole population including targeted campaigns to reduce smoking among adults may have a role to play in the prevention of IMD in children.